Chronic Daily Headache: Ten Steps for Primary Care Providers to Regain Control. Issue 10 (23rd August 2016) - Sheeler, Robert D.; Garza, Ivan; Vargas, Bert B.; O'Neil, Angela E.
Abstract : Background: Chronic daily headache (CDH) affects 2% to 4% of the North American and European population. Various pathways lead to this condition, although chronification of migraine and the occurrence of central sensitization in tension headache are the 2 most common. Medication overuse headaches complicate a substantial portion of other primary headaches that have become chronic and often make their treatment more complex and less successful. Methods/Results: A 10‐step process to help primary care providers evaluate and treat CDH patients begins with excluding secondary headache disorders, then moves on to classification of the primary underlying headache disorder. Next, the exacerbating factors, as well as relevant comorbid conditions, are identified. The patient's current acute therapy is examined, and attempts are made to identify and resolve medication overuse if present. Past preventive therapies are reviewed, allowing for thoughtful design of a headache action plan with preventive, acute, and lifestyle components. Patients are asked to keep a headache diary, used to initiate a cycle of continuous improvement in a patient's response to acute and preventive therapeutic approaches. Conclusions: A systematic approach and partnership with patients often make it possible to convert CDH to episodic headache that is responsive to both acute and preventive therapies.